CHANGES IN THE ORAL MUCOSA UNDER THE INFLUENCE OF LOW-FREQUENCY ELECTROMAGNETIC RADIATION - Markovska, I.V.; Sokolova, I.I.; Garmash, O.V.; Savieliieva, N.N.; Tomilina, T.V.; Shapkyn, A.S. (World of Medicine and Biology, 2024)
The study was devoted to analyze the condition of the oral mucosa under the influence of low-frequency (70 kHz) industrial frequency electromagnetic radiation in the clinical setting (111 individuals – workers of the Kharkiv Tractor Plant) and in the experimental part (36 laboratory rats of the WAG-populational). The results of the clinical and experimental examination confirm the negative impact of prolonged professional exposure to electromagnetic radiation both on the oral mucosa of patients and laboratory animals, which requires implementation of therapeutic and preventive measures.
Keywords: oral mucosa; low-frequency electromagnetic radiation; occupational exposure; oral lichen planus; recurrent aphthous stomatitis